2012
DOI: 10.3928/01477447-20120222-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phenol and Argon Beam Coagulation as Adjuvant Therapies in the Treatment of Stage 2 and 3 Benign–Aggressive Bone Tumors

Abstract: Argon beam photocoagulation has gained popularity as an adjuvant therapy for the treatment of giant cell tumors of bone and other stage 2 or 3 benign-aggressive bone tumors. Although argon beam photocoagulation has been considered a safe and reasonable adjuvant treatment with acceptable recurrence rates, it has never been directly compared with the commonly described phenol as adjuvant. The purpose of this study was to determine whether argon beam photocoagulation is as effective as phenol in preventing recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
1
20
0
2
Order By: Relevance
“…Van et al [ 15 ] believed that the exothermic reaction of PMMA is a risk factor for the development of osteoarthritis. Similar results were reported by Chen et al [ 23 ] and Joseph et al [ 24 ] Currently, PMMA is widely used for cavity filling and structural reconstruction in GCTB and some low-grade malignant bone tumors and is believed to be associated with a high rate of osteoarthritis. [ 1 , 3 , 21 ] However, some remedies might be available to prevent heat necrosis and problems related to the mechanical properties of PMMA.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Van et al [ 15 ] believed that the exothermic reaction of PMMA is a risk factor for the development of osteoarthritis. Similar results were reported by Chen et al [ 23 ] and Joseph et al [ 24 ] Currently, PMMA is widely used for cavity filling and structural reconstruction in GCTB and some low-grade malignant bone tumors and is believed to be associated with a high rate of osteoarthritis. [ 1 , 3 , 21 ] However, some remedies might be available to prevent heat necrosis and problems related to the mechanical properties of PMMA.…”
Section: Introductionsupporting
confidence: 84%
“…Similarly, Van et al [ 15 ] found that the function and quality of life of patients with KL3-4 were comparable with those of patients with KL0-2, suggesting that radiographic findings of osteoarthritis identified at a mid-term follow-up persisted. Joseph et al [ 24 ] found that compared with PMMA alone, the use of periarticular bone graft constructions reduces postoperative osteoarthritis without increasing the likelihood of tumor recurrence. However, there remains a lack of consensus concerning the need for fixation when intralesional curettage is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Curettage with PMMA has been associated with local recurrence rates of 0–29% [ 46 , 61 , 63 – 65 , 68 75 , 90 , 91 ]; when combined with local phenol application the local recurrence rates are 3–33% [ 46 , 61 , 63 – 65 , 69 , 71 – 74 ]. Local recurrences can be treated with repeat curettage, phenol, and PMMA, with re-recurrence rates of 9–34% (mean: 19%) [ 61 , 64 67 , 72 , 73 , 76 80 ]. Cryoablation with liquid nitrogen is associated with local recurrence rates of 8–42% (mean: 21%) and 0–20% (mean: 6%) when combined with bone grafts and PMMA [ 60 , 65 , 70 , 72 , 81 – 99 ].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Tissue desiccation causes tissue carbonization, thus the cavity tends to assume a characteristic dark colouring. As data in medical literature confirm, this technique is easier to manage than others [25]; In fact argon beam coagulation has been considered a safe and reasonable adjuvant treatment with low recurrence rates.…”
Section: Argon Beam Coagulationmentioning
confidence: 93%